453 Intraoperative electron radiation therapy (IOERT) in the management of patients with local recurrent or advanced ginecologic malignancies: a six case review. (18th September 2019) - Sousa, F; Sousa, O; Salgado, L; Castro, B; Ramos, T; Castro, C; Soares, A; Carvalho, L
Abstract : Objectives: To report outcomes and toxicities in women with locally recurrent or advanced pelvic gynecologic malignancies who received intraoperative electron beam radiotherapy (IOERT) after chemoradiation. Methods: From April 2012 to October 2018, 6 patients with recurrent cervical cancer (n=3), vagina (n=2) and endometrial (n=1) were treated with IOERT (stage IIb-IVb). Previously unirradiated (n=2) patients received preoperative chemoradiation between 45–50.4Gy with cisplatin. Those who had already been irradiated (n=4) received 30Gy to pelvis with concomitant cisplatin. IOERT dose ranged between 10Gy–15Gy. Results: With a median follow-up of 55 months (range, 24–162) the 3-year overall survival was 100%. The median time from initial cancer diagnosis to recurrence treated with IOERT was 4.1 years (range, 1.4–10.3 years). Performed surgeries included pelvic exenteration (n=3) and posterior pelvic exenteration (n=3) with or without lymph node dissection. All surgeries had gross macroscopic resections and were classified as R0 (n=5; 83.3%) or R1 (n=1; 16.6%). All patients remain disease free. No major IOERT-related toxicities were reported. Conclusions: Radical resection combined with IOERT seems to be a valid curative treatment option for patients who have failed prior surgery and/or definitive radiation. The patient selection is crucial and in addition to consideration of disease related morbidity, other factors shall be considered including the time interval from initial therapy to recurrence and whether the patient is able to receive perioperative chemoradiation and pelvic exenteration in addition to IOERT.